Preoperative Cyanoacrylate Embolization of Venous Malformations - Monroe, Eric J.; Chewning, Rush; Koo, Kevin S. H.; Shivaram, Giri (Journal of Clinical Interventional Radiology ISVIR, 2018)
Percutaneous sclerotherapy and standalone surgical excision have historically been the mainstay of treatment for pediatric venous malformations (VMs). However, both approaches have significant limitations. Sclerotherapy often requires multiple treatment sessions, with each round adding additional procedural and anesthetic risks as well as radiation exposure. Standalone surgical excision of VMs can be complicated by high-volume blood loss, and indistinct lesion margins can lead to incomplete resection, resulting in recurrence. An alternative to these approaches is percutaneous cyanoacrylate glue embolization followed by immediate surgical excision, a single-stage procedure that allows for better surgical margin definition and reduced intraoperative blood loss, potentially leading to more definitive treatment. The authors describe the interventional radiology aspects of this combined procedure, emphasizing materials preparation and embolization technique.
Keywords: venous malformation; embolization; n-butyl cyanoacrylate